Communicating process architectures 2011 WoTUG-33 : proceedings of the 33rd WoTUG Technical Meeting, 19-22 June 2011, University of Limerick, Ireland / edited by Peter H. Welch ... [et al.]. [electronic resource] : (2011)
Summary goes here